2004
DOI: 10.1111/j.0965-075x.2004.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Fairness in Personnel Selection: Determinants and Outcomes in Different Stages of the Assessment Procedure

Abstract: This study addresses the determinants and outcomes of fairness perceptions in a real assessment procedure as performed by a selection agency. Fairness perceptions were investigated at three points in time: before the assessment, right after the assessment but before assessment feedback, and after assessment feedback. Using structural equation modeling, we tested how fairness perceptions develop throughout the assessment procedure. Applicants' openness to experiences affected their test beliefs before the actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 55 publications
3
39
1
Order By: Relevance
“…In terms of the AART of Ployhart and Harold (2004), favourable testing conditions (selection procedure justice) may counteract the attribution trigger, resulting in a critical stance towards individual tests. The forced-choice-item format of the personality test used in this study had the potential of eliciting negative responses as the perceived influence over the outcome of the assessment was reduced (Van Vianen et al, 2004). However, it appears that this may not have differentially skewed TAs in favour of the cognitive ability tests because of the compensatory effects of using the tests in combination (Rosse et al, 1994).…”
Section: Outline Of the Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In terms of the AART of Ployhart and Harold (2004), favourable testing conditions (selection procedure justice) may counteract the attribution trigger, resulting in a critical stance towards individual tests. The forced-choice-item format of the personality test used in this study had the potential of eliciting negative responses as the perceived influence over the outcome of the assessment was reduced (Van Vianen et al, 2004). However, it appears that this may not have differentially skewed TAs in favour of the cognitive ability tests because of the compensatory effects of using the tests in combination (Rosse et al, 1994).…”
Section: Outline Of the Resultsmentioning
confidence: 93%
“…However, it may be argued that the more negative TA of sales position applicants may be attributable to self-serving bias formed by a negative perception of perceived performance in a test that they may have experienced as difficult (Whitman et al, 2014). Job applicants generally view personality tests as more controllable than cognitive ability tests, which may contribute to self-serving bias manifesting as a negative TA towards a cognitive ability test that is perceived as particularly difficult and consequently less valid (Van Vianen et al, 2004). Steiner and Gilliland (1996) argue that people judge implicitly that widely used testing techniques must be valid, resulting in a favourable view of tests (belief in tests).…”
Section: Outline Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many situations it is happening that applicants are being influenced by their experiences from already appeared selection procedures and ISSN 2162-3058 2015 www.macrothink.org/ijhrs 138 also how they perform in the present situation (chan et al, 1997). Vianen et al, (2004) highlighed that in making selection of an employee the situational judgment test has higher rating as compare to the cognitive ability and personality test. Sonja Schinkel et al, (2004) found that feedback has relevance with the procedural fairness but the problem is that how to give feedback of their performance in case of rejection decision which is generally assumed not good for the organization.…”
Section: Fairness and Procedural Justice Issue In The Recruitment Andmentioning
confidence: 99%
“…I am aware of only one study that that has investigated quantitative changes in individual reactions at more than two time points. In that study, van Vianen, Taris, Scholten and Schinkel (2004) examined applicant reactions at three time points throughout the selection process and found that perceived performance directly affected postfeedback fairness perceptions, rather than affecting fairness through perceptions of job relatedness. They thus suggested that self-serving bias was in effect and called for Self-Serving Bias 3 more research into the specific elements and processes that provide the basis for selfserving bias effects.…”
mentioning
confidence: 99%